SISTEM PENUNJANG KEPUTUSAN PEMILIHAN GENERATOR SET YANG SESUAI KEBUTUHAN CALON KONSUMEN MENGGUNAKAN METODE TOPSIS PADA PT. SINAR TEKNIK PRATAMA - Muhammad Rizaldy; Bianca Resna Maya Sari; Dikwan Moeis (P3M STMIK Profesional Makassar, 2022)
The purpose of this study is that there is a problem regarding the selection of generators that are suitable for home needs, therefore we want to help consumers to find generators that suit the needs and capacity of their homes. The method in solving this problem, namely, the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is a compensation aggregation method that compares a series of alternatives by identifying the weights for each criterion, normalizing the score for each criterion and calculating the geometric distance between each alternative and the ideal alternative, which is the best score for each criterion. The result of this research is the system can find out which generators are in accordance with consumer needs and which are not in accordance with consumer needs.